Differential Bone Loss in Mouse Models of Colon Cancer Cachexia - Bonetto, Andrea; Kays, Joshua K.; Parker, Valorie A.; Matthews, Ryan R.; Barreto, Rafael; Puppa, Melissa J.; Kang, Kyung S.; Carson, James A.; Guise, Theresa A.; Mohammad, Khalid S.; Robling, Alexander G.; Couch, Marion E.; et al. (Frontiers in Physiology, 2017)
Cachexia is a distinctive feature of colorectal cancer associated with body weight loss and progressive muscle wasting. Several mechanisms responsible for muscle and fat wasting have been identified, however it is not known whether the physiologic and molecular crosstalk between muscle and bone tissue may also contribute to the cachectic phenotype in cancer patients. The purpose of this study was to clarify whether tumor growth associates with bone loss using several experimental models of colorectal cancer cachexia, namely C26, HT-29 and ApcMin/+. The effects of cachexia on bone structure and strength were evaluated with dual energy X-ray absorptiometry (DXA), micro computed tomography (μCT), and three-point bending test. We found that all models showed tumor growth consistent with severe cachexia. While muscle wasting in C26 hosts was accompanied by moderate bone depletion, no loss of bone strength was observed. However, HT-29 tumor bearing mice showed bone abnormalities including significant reductions in whole-body bone mineral density (BMD), bone mineral content (BMC), femoral trabecular bone volume fraction (BV/TV), trabecular number (Tb.N), and trabecular thickness (Tb.Th), but no declines in strength. Similarly, cachexia in the ApcMin/+ mice was associated with significant decreases in BMD, BMC, BV/TV, Tb.N, and Tb.Th as well as decreased strength. Our data suggest that colorectal cancer is associated with muscle wasting and may be accompanied by bone loss dependent upon tumor type, burden, stage and duration of the disease. It is clear that preserving muscle mass promotes survival in cancer cachexia. Future studies will determine whether strategies aimed at preventing bone loss can also improve outcomes and survival in colorectal cancer cachexia.